‘Kha Me’Jatra of Bhaktapur: An Intangible Cultural Heritage of Nepal - Dulal, Lok Nath (Literary Studies, 2021)
The main aim of this paper is to explore and highlight the Kha Me Jatra as an important intangible cultural heritage of Bhaktapur and Nepal as well. Not only status and glory, but the unique identity of our nation is also represented by the temples, monasteries, images, feasts, festivals, the mountains, rivers, forests, lakes as well as various beautiful places. These globally renowned properties have made our nation peculiar, popular and prestigious in the world. Nepalese people observe and commonly participate the celebration of many wonderful festivals and fairs celebrated in different parts and days in the year. For instance, people of Bhaktapur celebrate different colorful festivals and Jatras on the special auspicious days of every year. Every festive event of Bhaktapur has its own specialties. Through the perspective of intangible cultural heritage among them, Kha Me is one of the important Jatra which is celebrated on the ninth day of Dashain, the greatest festival of Nepal. ‘Kha Me’ is a pure male buffalo which is reared in the name of goddess Bramhayani in Bhaktapur. It is brought in Gathemunga festival and kept in the ground floor of the temple of goddess Durga. During the ninth day it is taken in an open street for the procession. It is a typical Jatra which represents indigenous feature and identity of Bhaktapur, the cultural capital of Nepal. But, unfortunately, this peculiar and popular festival has still remained an untouched issue of the academia. No one has explored and highlighted it as an intangible cultural heritage from the perspectives of cultural, religious and social significance.